2020
DOI: 10.21037/jtd.2020.04.21
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of MET exon 14 skipping mutations in non-small cell lung cancer according to technical approach in routine diagnosis: results from a real-life cohort of 2,369 patients

Abstract: Background: Mesenchymal epithelial transition receptor (MET) alterations, including MET exon 14 skipping mutation, are oncogenic in non-small cell lung cancer (NSCLC) and may confer sensitivity to targeted therapy. Given the rarity and the diversity of exon 14 skipping mutations, diagnosis may be challenging on small-biopsy specimens. Methods: Between March 2014 and May 2018, tissue samples from patients with metastatic NSCLC were analysed for MET exon 14 skipping mutation as part of routine practice in the Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…To validate the MET14 discovery potential of the above-described NN, we used a set of 690 RNAseq samples from the TCGA bronchus and lung dataset. The 690 samples were manually inspected using the Broad's integrative genomics viewer [18] and we detected 17 exon 14 skipping events (2.4%), which is in line with the frequency of the exon 14 skipping events observed by Champagnac [8]. We tested on this tumor set the NN trained with k-mer counts frequency, which predicted 4 samples out of 17 as MET14, but only one was a real exon skipping events (sensitivity 5.88%, specificity 99.5%, supplementary table 2S).…”
Section: Neural Network Validation and Discovery On Tcga Samplessupporting
confidence: 77%
See 1 more Smart Citation
“…To validate the MET14 discovery potential of the above-described NN, we used a set of 690 RNAseq samples from the TCGA bronchus and lung dataset. The 690 samples were manually inspected using the Broad's integrative genomics viewer [18] and we detected 17 exon 14 skipping events (2.4%), which is in line with the frequency of the exon 14 skipping events observed by Champagnac [8]. We tested on this tumor set the NN trained with k-mer counts frequency, which predicted 4 samples out of 17 as MET14, but only one was a real exon skipping events (sensitivity 5.88%, specificity 99.5%, supplementary table 2S).…”
Section: Neural Network Validation and Discovery On Tcga Samplessupporting
confidence: 77%
“…Notably, MET exon 14 skipping is the only ES event encompassing a massive number of citations (119 from 2015 to 2021 reported in the PUB-MED repository). Champagnac and coworkers [8] observed that genomic alterations affecting MET exon 14 are present in 2.6% of non-small cell lung cancer (NSCLC) patients. MET exon 14 skipping can lead to acquisition of transforming ability and has been identified as potential therapeutic target for NSCLC [9].…”
Section: Introductionmentioning
confidence: 99%
“…57,62,63 Approximately 3-4% of NSCLCs harbor the METex14 alteration (Table 1). 18,57,[63][64][65][66][67][68] They are associated with some histologic subtypes of NSCLC but are not related to tumor stage. Among the histological subtypes, METex14 skipping alteration is commonly found in sarcomatoid carcinoma (4.9-31%), [69][70][71][72] adenosquamous carcinoma (4-8%), 18,73,74 adenocarcinoma (3-4%), 1,18,57,65,75,76 and squamous cell carcinoma (2%).…”
Section: Metex14 Skipping Alteration In Nsclcmentioning
confidence: 99%
“…83 In ideal cases, both DNA-and RNAbased assays are used to complement each other for reliable detection of METex14 alterations (Table 1). 1,18,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Reverse transcription polymerase chain reaction (RT-PCR), quantitative real time RT-PCR, and Sanger sequencing are the routine approaches used for the analysis of mutations and METex14 alteration. 18,73 mRNA transcript can be reverse transcribed using RT-PCR and corresponding complementary DNA is sequenced using Sanger techniques to verify exon 14 skipping from the sample.…”
Section: Metex14 Skipping Alteration In Nsclcmentioning
confidence: 99%
“…MET exon 14 skipping was described in lung adenocarcinoma (3%), other lung neoplasms than adenocarcinomas (2.3%), brain glioma (0.4%), and tumors of unknown primary origin (0.4%) [ 8 ]. Furthermore, Champagnac and coworkers [ 10 ] observed that genomic alterations affecting MET exon 14 are present in 2.6% of non-small cell lung cancer (NSCLC) patients. MET exon 14 skipping can lead to acquisition of transforming ability and was identified as a potential therapeutic target for NSCLC [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%